Logistics Commitment: An Evidence of Long-term Relationship on Sustainable Global Supply Chain - Idris, Sidah; Mohezar, Suhana (International Journal of Engineering and Technology, 2018)
Manufactures and all network partners may think that global supply chains are simple and direct. But, in the vast majority of cases, this is not the case. Customer demand is supported by complex and lengthy global supply chain. The intermodal transportations provide the key success of the connections between global factories and along the supply chain parties. While they provide critical services, each level of transportation will present challenge and difficulty to all parties. This study look on how logistics commitment can improves operating efficiencies among local manufacturers and service providers as they are in global supply chain network. And, how each intermodal invested improve capabilities, creating reliable and economical port-to-destination delivery services in ensure good relationship with their partners. The study aims is to identify how the service providers can reshape relationship and revise networks to maintain smooth and efficient global logistics flows. This empirical study will use survey questionnaire to get the answer for each question and utilize Partial Least Square (PLS) to analyse the data. Result shows how logistics commitment effort and strategy as to sustain global supply chain relationship.